1973
DOI: 10.7589/0090-3558-9.2.111
|View full text |Cite
|
Sign up to set email alerts
|

A POXVIRUS ISOLATED FROM SILVEREYES (Zosterops lateralis) FROM LOWER HUTT, NEW ZEALAND

Abstract: Poxviruses were isolated from skin lesions of eight silvereyes during 1969-71. In all cases, characteristic virus particles were seen in extracts of the lesions and all isolates produced pocks on the chorioailantoic membrane of embryonated chicken eggs. Comparison by immunodiffusion showed that the viruses were antigenically identical, and that they differed from poxviruses recently isolated from domestic fowls, pigeons and a canary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In New Zealand, avipoxviruses were isolated from silvereyes (1), and a second report has been recorded of pox-like lesions in pipits (20). Thus although most reports have been based on observations of pox-like lesions suggesting that pox infections may be relatively common in wild birds in the Australasian region, there have been three reports of isolations from magpies (7, 12) and silvereyes (1).…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, avipoxviruses were isolated from silvereyes (1), and a second report has been recorded of pox-like lesions in pipits (20). Thus although most reports have been based on observations of pox-like lesions suggesting that pox infections may be relatively common in wild birds in the Australasian region, there have been three reports of isolations from magpies (7, 12) and silvereyes (1).…”
Section: Discussionmentioning
confidence: 99%
“…'Indigenous' also has social, cultural, and scientific context shifts, as it is heavily influenced by the wider environment and understanding [31]. For instance, the bird Zosterops lateralis (silvereye or wax-eye/tauhou, meaning 'new arrival' in te reo Māori) is considered an indigenous species despite reportedly only arriving in Aotearoa New Zealand in the 1800s [32][33][34]. Although this study has distinguished viruses associated with indigenous and exotic species, some changes to virus designation may arise if new research reveals an alternative arrival history of a host.…”
Section: Indigenous and Endemic Viruses Of Aotearoa New Zealandmentioning
confidence: 99%
“…The vertebrate poxviruses are divided into eight genera (Moyer et al 2000), and in New Zealand, poxviruses of the avipoxvirus (Austin et al 1973) and parapoxvirus genera have been reported in animals. The parapoxviruses in New Zealand include pseudocowpox virus (PCPV) and bovine papular stomatitis virus (BPSV) affecting cattle, orf virus or contagious ecthyma mainly affecting sheep, and parapoxvirus of red deer (Cervus elaphus) (PVNZ) (Horner et al 1987;Mercer and Haig 1999).…”
Section: Introductionmentioning
confidence: 99%